Strategic perspective of error management, the role of leadership, and an error management culture: A mediation model - Margarida Freitas Oliveira; Eulália Santos; Vanessa Ratten (Journal of Economics, Finance and Administrative Science, 2023)
Purpose - Errors are inevitable, resulting from the human condition itself, system failures and the interaction of both. It is essential to know how to deal with their occurrence, managing them. However, the negative tone associated with them makes it difficult for most organizations to talk about mistakes clearly and transparently, for fear of being harmed, preventing their detection, treatment and recovery. Consequently, errors are not managed, remaining accumulated in the system, turning into successive failures. Organizations need to recognize the inevitability of errors, making the system robust, through leadership and an organizational culture of error management. This study aims to understand the role of these influencing variables in an error management approach. Design/methodology/approach - In this paper, the authors applied the methodology of a quantitative nature based on a questionnaire survey that analyses error management, leadership and the organizational culture of error management of 380 workers in Portuguese companies. Findings - The results demonstrate that leadership directly influences error management and indirectly through the organizational culture of error management, giving this last variable a mediating role. Originality/value - The study covers companies from different sectors of activity on a topic that is little explored in Portugal, but part of the daily life of organizations, which should deserve greater attention from directors and managers, as they assume a privileged position to promote and develop error management mechanisms. Error management must be the daily work of leaders. This study contributes to theoretical knowledge and business practice on error management.
Keywords: 330; Error management; Leadership; Organizational culture error management